Functionalized Ruthenium Complexes: Selective "Turn‐on" Detection of Biologically Relevant Anionic Species. Issue 25 (3rd July 2017) - Berni, Emanuela; Le Henaff, Laurent; Jarrige, Lucie; Girard, Emeline; Jonusauskas, Gediminas; Gosse, Isabelle; Pinet, Sandra
Abstract : To study the effect of the structure of 3, 3′‐modified bipyridyl ruthenium complexes on their ability to recognize organic anions, various ruthenium complexes have been prepared. The binding functions and large‐sized modified bipyridyl ligand turned out to be essential for selectivity in acetonitrile. The selectivity for dicarboxylates or phosphates can be switched by using guanidinium‐ or ammonium‐functionalized probes. One of these probes turned out to be selective towards glutamate over aspartate and γ‐aminobutyric acid (GABA). Another was selective towards adenosine 5′‐triphosphate (ATP) over adenosine 5′‐diphosphate (ADP), pyrophosphate (PPi), adenosine 5′‐monophosphate (AMP), and orthophosphate (Pi). In both cases, the binding was attributed to coulombic interactions and hydrogen bonding. π‐stacking interactions also occurred with nucleotides. Replacing ammonium by zinc‐dipicolylamine units made possible the recognition of phosphorylated species in buffered aqueous systems. To our delight, this probe showed selectivity for ADP over ATP and we proved that the selectivity was partly due to substitution at the 3‐ and 3′‐positions of the ligand. Abstract : New 3, 3′‐bipyridyl‐modified ruthenium luminescent probes have been designed for the detection of biologically relevant anions in organic and aqueous media. Interestingly, in pure Hepes buffer, one of these probes responds selectively to micromolar concentrations of adenosine diphosphate.